2010
DOI: 10.1148/radiol.09090838
|View full text |Cite
|
Sign up to set email alerts
|

Cancerous Breast Lesions on Dynamic Contrast-enhanced MR Images: Computerized Characterization for Image-based Prognostic Markers

Abstract: Purpose:To assess the performance of computer-extracted dynamic contrast material-enhanced (DCE) magnetic resonance (MR) imaging kinetic and morphologic features in the differentiation of invasive versus noninvasive breast lesions and metastatic versus nonmetastatic breast lesions. Materials and Methods:In this institutional review board-approved HIPAA-compliant study, in which the requirement for informed patient consent was waived, breast MR images were retrospectively collected. The images had been obtained… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
157
0
2

Year Published

2012
2012
2015
2015

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 178 publications
(163 citation statements)
references
References 52 publications
4
157
0
2
Order By: Relevance
“…Thirdly, more morphological features can be extracted around the tumor region to have more understanding of the relation between vascularity and the likelihood of tumor malignancy. Finally, our vascular features might also be used as prognostic markers to differentiate different histology [37,38].…”
Section: Discussionmentioning
confidence: 99%
“…Thirdly, more morphological features can be extracted around the tumor region to have more understanding of the relation between vascularity and the likelihood of tumor malignancy. Finally, our vascular features might also be used as prognostic markers to differentiate different histology [37,38].…”
Section: Discussionmentioning
confidence: 99%
“…In the last two decades, several experimental studies have demonstrated that quantitative methods (based on tracer kinetics modelling) can be more specific in distinguishing benign from malignant breast disease, because of the capability to derive parameters strictly related to tissue microvasculature without any operator dependency [19,[20][21][22][23][24][28][29][30][31][32][33][34][35][36][37][38][39][40][41]. However, as there is not yet sufficient standardisation of quantitative methods, semi-quantitative approaches have been used because they could represent a compromise between qualitative and quantitative approaches.…”
Section: Discussionmentioning
confidence: 99%
“…41,42 FCM is a data clustering scheme similar to k-means in that data are clustered around a prescribed number of centroids. However, unlike k-means, the resulting class membership is a fuzzy membership to each cluster.…”
Section: Vic1 Fuzzy C-meansmentioning
confidence: 99%